The strategic role of the regional house of representatives (DPRD) in promoting sustainable development in the buffer zones of the national capital city - KA, Abdurahman; Paselle, Enos (Lembaga Riset Mutiara Akbar, 2026)
he relocation of the Indonesian National Capital (IKN) to East Kalimantan is a strategic policy aimed at promoting equitable development and realizing a sustainable city. In this context, the buffer zone plays a crucial role as a supporting area that must be managed in an integrated manner. This study aims to analyze the role of the Regional Representative Council (DPRD) of East Kalimantan Province in promoting sustainable development in the IKN buffer zone, examine the strategies implemented, and identify the obstacles encountered. The study used a qualitative approach with a case study method, through data collection techniques such as in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman interactive model. The results show that the DPRD has a strategic role through its legislative, budgeting, and oversight functions. However, the effectiveness of this role is still hampered by weak policy integration, limited cross-sectoral coordination, a suboptimal data-based information system, and the weak application of sustainable development principles in regional policies. Therefore, it is necessary to strengthen the DPRD's institutional capacity, improve development data integration, and collaborate among stakeholders to realize sustainable development governance.